Peningkatan Keterampilan Guru dalam Memanfaatkan Google Form sebagai Media Evaluasi Pembelajaran Jarak Jauh - Umar Mansyur; Erick Irawadi Alwi; Ihramsari Akidah (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
The problem with the partner, MTs Wihdatul Ulum Bontokassi, Gowa Regency, is that the implementation of learning evaluation activities during the Covid-19 pandemic or distance learning has not been based online. Most teachers also do not understand the benefits of google forms in learning activities. For this reason, the solution applied is to provide training on the use of Google Forms as a learning evaluation medium, so that teacher competence can be increased. The method used is training and practice. In addition, teachers are provided with training modules and google form video tutorials. The results of community service activities show that teachers have been able to use google forms in evaluating their online learning at school. This is in line with the results of the questionnaire analysis of the evaluation of service activities which showed as many as 76.2% of the training participants stated that they had increased their skills in compiling learning evaluation media using google form on a greatly improved rating scale.